Association mapping and identification of candidate genes for callus induction and regeneration using sorghum mature seeds - Xu, Jingyi; Wang, Lihua; Liang, Yuan; Shen, Qi; Tu, Wenmiao; Cheng, Zhengxiao; Hu, Lu; Wang, Yi-Hong; Li, Jieqin (Frontiers in Plant Science, 2025)
IntroductionA whole plant can be regenerated through tissue culture from an embryogenic callus in a process referred to as plant regeneration. Regeneration ability of embryogenic callus is a quantitative trait and the main limiting factor for genetic studies in sorghum.MethodsWe evaluated 236 sorghum mini core varieties for callus induction rate, embryogenic callus rate, callus browning rate and differentiation rate and performed a multi-locus genome-wide association study (GWAS) of the four traits with 6,094,317 SNPs.ResultsWe found five mini core varieties most amenable to tissue culture manipulations: IS5667, IS24503, IS8348, IS4698, and IS5295.Furthermore, we mapped 34 quantitative trait loci (QTLs) to the four traits and identified 47 candidate genes. Previous studies provided evidence for the orthologs of 14 of these genes for their role in cellular function and embryogenesis and that the ortholog of WIND1 (WOUND INDUCED DEDIFFERENTIATION 1) identified in this study promotes callus formation and increases de novo shoot regeneration.ConclusionThese candidate genes will help to further understand the genetic basis of plant embryonic callus regeneration.